Matthew and the midnight pirates - Morgan, Allen, 1946-; Martchenko, Michael (Toronto; New York : Stoddart Kids, 1998)
"When Matthew hears that library fines might be increasing, he frets over an overdue pirate book. A busload of pirates arrives, and they embark on a midnight mission to save the city's books" Cf. Our choice, 1998-1999.
Keywords: Pirates -- Fiction; Holmes, Matthew (Fictitious character) -- Juvenile fiction; Pirates -- Juvenile fiction; Libraries -- Juvenile fiction; Night -- Juvenile fiction; Picture books for children; Holmes, Mathieu (Personnage fictif) -- Romans, nouvelles, etc. pour la jeunesse; Pirates -- Romans, nouvelles, etc. pour la jeunesse; v; Nuit -- Romans, nouvelles, etc. pour la jeunesse; Livres d'images pour enfants